Successes and Issues in the Growth of Moad and MoSe2 on Ag(111) by the E-ALD Method - Martina Vizza; Andrea Giaccherini; Walter Giurlani; Maurizio Passaponti; Nicola Cioffi; Rosaria Anna Picca; Antonio De Luca; Lorenzo Fabbri; Alessandro Lavacchi; Filippo Gambinossi; Emanuele Piciollo; Emanuele Salvietti; et al. (Metals, 2019)
This paper explores the conditions for the electrodeposition of Moad (molybdenum adlayer) on Ag(111) from alkaline aqueous solution. Moreover, the first stages of the growth of MoSe2 are also presented, performing the deposition of Sead on the deposited Moad. The deposition of Moad on Sead/Ag(111) was also explored. MoSe2 is of interest due to its peculiar optoelectronic properties, making it suitable for solar energy conversion and nanoelectronics. In this study, electrodeposition techniques were exploited for the synthesis process as more sustainable alternatives to vacuum based techniques. The electrochemical atomic layer deposition (E-ALD) method emerges as a suitable technique to grow inorganic semiconductor thin films thanks to its fulfillment of the green energy predicament and a strict structural and morphological control, and this approach has gathered the attention of the scientific community. Indeed, E-ALD exploits surface limited reactions (SLRs) to alternate the deposition of chemically different atomic layers constituting a compound semiconductor. Thus, E-ALD is one of the most promising electrodeposition techniques for the growth of thin-film of compound semiconductors under a strict structural and morphological control. On this ground, E-ALD can be considered an ideal technique for the growth of 2D materials.